The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fpls.2023.1163195
|View full text |Cite
|
Sign up to set email alerts
|

Biomass composite with exogenous organic acid addition supports the growth of sweet sorghum (Sorghum bicolor ‘Dochna’) by reducing salinity and increasing nutrient levels in coastal saline–alkaline soil

Abstract: IntroductionIn coastal saline lands, organic matter is scarce and saline stress is high. Exploring the promotion effect of intervention with organic acid from biological materials on soil improvement and thus forage output and determining the related mechanism are beneficial to the potential cultivation and resourceful, high-value utilization of coastal mudflats as back-up arable land.MethodThree exogenous organic acids [humic acid (H), fulvic acid (F), and citric acid (C)] were combined with four kinds of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 115 publications
(122 reference statements)
0
0
0
Order By: Relevance
“…Trichoderma are recognized as synthesizers of phytohormones, such as auxin, and hormone-like compounds called harzianolide, substances that, together with auxin, act to expand the cell wall and increase biomass production by plants [97,98]. OM acts as a source of nutrients, soil conditioner, and food for the soil microbiota, and these characteristics improve fertility, soil aggregation, and nutrient cycling, thus promoting better nutrition and more significant biomass accumulation by sorghum [99,100]. The productivity obtained in this study is compatible with that found even when forage sorghum is irrigated with good-quality water [101][102][103].…”
Section: Sorghum Yield and Water Use Efficiencymentioning
confidence: 99%
“…Trichoderma are recognized as synthesizers of phytohormones, such as auxin, and hormone-like compounds called harzianolide, substances that, together with auxin, act to expand the cell wall and increase biomass production by plants [97,98]. OM acts as a source of nutrients, soil conditioner, and food for the soil microbiota, and these characteristics improve fertility, soil aggregation, and nutrient cycling, thus promoting better nutrition and more significant biomass accumulation by sorghum [99,100]. The productivity obtained in this study is compatible with that found even when forage sorghum is irrigated with good-quality water [101][102][103].…”
Section: Sorghum Yield and Water Use Efficiencymentioning
confidence: 99%
“…The specific physicochemical properties are shown in Table 1. The area has a subtropical monsoon maritime climate with an average annual temperature of 16.3°C and an average annual precipitation of 1,024 mm, which mainly occurs in summer (Wang et al, 2023;Yang et al, 2023).…”
Section: Experimental Sitementioning
confidence: 99%
“…It was found that exogenously applied organic acids can adjust the acid -base and redox conditions of soil tillage using acidic functional groups, adsorb soil saline ions through chelation, and enhance the solubility and mobility of phosphorus, thus promoting the enhancement of effective nutrients in saline soils (Chatterjee et al, 2015). Consequently, it may be due to the addition of exogenous substances to improve the soil microbial survival of the adverse environmental conditions, such as soil structure, pH, aeration and permeability, and topsoil nutrient composition changes (Yang et al, 2023), the improvement of the adverse environmental conditions makes most of the bacterial community's more easy to grow and reproduce, which adjusts the species and number of various bacterial groups in the soil, resulting in the bacterial community development direction differences, changing the diversity of the community. However, short-term application cannot easily have a significant effect on bacterial community diversity due to the relatively stable structure of organic materials (Wu et al, 2013).…”
Section: Effects Of Exogenous Organic Acids and Biological Substrates...mentioning
confidence: 99%
“…Humic acid is derived from plant materials that are comparable to biochar. However, humic acid has more active organic materials that can enhance soil fertility [21], regulate the biological community [22], ameliorate soil aggregate compositions [23], increase fertilizer utilization efficiency [24], and improve seedling growth [25] in saline soils. The abundant functional groups of humic acid allow it to form complexes with ions, thus reducing salt toxicity [26].…”
Section: Introductionmentioning
confidence: 99%